Piety and patienthood in medieval Islam - Ragab, Ahmed, author.
1 online resource (256 pages).
Keywords: How did pious medieval Muslims experience health and disease? Rooted in the prophet’s experiences with medicine and healing, Muslim pietistic literature developed cosmologies in which physical suffering and medical interventions interacted with religious obligations and spiritual health. This book traces the development of prophetic medical literature and religious writings around health and disease to give a new perspective on how patienthood was conditioned by the intersection of medicine and Islam.